Determinan Kecurangan Laporan Keuangan pada Bank Umum Syariah Periode 2014-2019 dalam Perspektif Fraud Triangle Theory - Febril Des Saputra Dini; Ine Mayasari; Fatmi Hadiani (Journal of Applied Islamic Economics and Finance, 2022)
The development of Islamic Commercial Banks in Indonesia shows good numbers. This is an opportunity for parties related to banking institutions to ensure this potential can be utilized to be developed again. However, in fact there are still Islamic banks that are caught incases fraud which can damage or disrupt the potential development of Islamic banking. This study aims to analyze the determinants of financial statement fraud in Islamic Commercial Banks registered in OJK for the 2014-2019 period with perspective Fraud Triangle Theory. This research usesmethods library and internet research. The sampling technique is a saturated sample consisting of 12 Islamic banks registered with the OJK. The analysis method is regression path analysis. The expected result of this study is an equation that can describe the influence of the independent variables, namely financial stability, financial target, external pressure, financial needs, ineffective monitoring, and rationalization. the dependent variable, namely earnings management.